Exploring the Druggability of Conserved RNA Regulatory Elements in the SARS‐CoV‐2 Genome. Issue 35 (3rd August 2021) - Sreeramulu, Sridhar; Richter, Christian; Berg, Hannes; Wirtz Martin, Maria A.; Ceylan, Betül; Matzel, Tobias; Adam, Jennifer; Altincekic, Nadide; Azzaoui, Kamal; Bains, Jasleen Kaur; Blommers, Marcel J. J.; Ferner, Jan; et al.
Abstract: SARS‐CoV‐2 contains a positive single‐stranded RNA genome of approximately 30 000 nucleotides. Within this genome, 15 RNA elements were identified as conserved between SARS‐CoV and SARS‐CoV‐2. By nuclear magnetic resonance (NMR) spectroscopy, we previously determined that these elements fold independently, in line with data from in vivo and ex‐vivo structural probing experiments. These elements contain non‐base‐paired regions that potentially harbor ligand‐binding pockets. Here, we performed an NMR‐based screening of a poised fragment library of 768 compounds for binding to these RNAs, employing three different 1 H‐based 1D NMR binding assays. The screening identified common as well as RNA‐element specific hits. The results allow selection of the most promising of the 15 RNA elements as putative drug targets. Based on the identified hits, we derive key functional units and groups in ligands for effective targeting of the RNA of SARS‐CoV‐2. Abstract : The RNA genome of SARS‐CoV‐2 contains 15 independently folded regulatory RNA elements. By NMR‐based fragment screening, the RNA target space for small molecule binding, functional mapping and inhibition is defined.